Non-Academic Constructs of Thai and Filipino 21st Century Teachers in the Thai Movie “Teacher’s Diary” - Aljon Delmo Galang (OKARA: Jurnal Bahasa dan Sastra, 2020)
Until the 21st Century, teachers are still seen in different constructs in countries such as the Philippines and Thailand. Though teachers' academic and non-academic roles are indispensably intertwined in the students' holistic development, the former roles are mostly the topic of query, clarification, and improvement, leaving the latter unclear. Nonetheless, the non-academic ones must be equally highlighted to educate the teaching force to achieve students' learning targets. Moreover, these roles lead to constructs, and these are seen in the modern representation of literary texts – films. In the Thai movie "Teacher's Diary," these non-academic constructs were perceived by the students. In analyzing the movie, to appreciate the literature world's cultural and aesthetic diversity, the participants identified these constructs emerging from their critical reflections. This study was made to discern and present non-academic constructs of the Thai and Filipino 21st Century teachers based on their written reflections. By using a qualitative approach, particularly content analysis, the non-academic constructs are revealed by students' critical reflection such as parental, vocational, epitomical, fortitudinous, and motivational constructs. In conclusion, teachers are seen as parents, servers, epitomes, enduring, encouraging, and inspiring. These provide insights to improve the teaching profession